PENGARUH KECERDASAN LOGIKA TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS MATERI SPLDV KELAS 10 DI SMK NEGERI 38 JAKARTA - Resta Aviani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Mathematical logical intelligence is the ability to calculate and reason in solving mathematical problems. Mathematical logical intelligence is closely related to students' abilities, especially in communicating mathematical solutions. Mathematical communication is a forum for students to obtain information and express mathematical concepts. Someone who has high mathematical logical intelligence will influence students' mathematical communication abilities in solving mathematical problems. The aim of this research is : 1. To find out the level of mathematical logical intelligence of class X students at SMKN 38 JAKARTA Academic Year 2024/2025, 2. To determine the level of mathematical communication skills of class X students at SMKN 38 JAKARTA for the 2024/2025 academic year, 3. To determine the significant influence of mathematical logical intelligence on students' mathematical communication abilities in solving three-variable linear equation systems at SMKN 38 JAKARTA for the 2024/2025 academic year. This research uses associative research with a quantitative approach. The data collection technique uses Cluster Random Sampling and data analysis uses simple linear regression.